Synthetic Dihydropyridines as Novel Antiacanthamoebic Agents - Anwar, Ayaz; Siddiqui, Ruqaiyyah; Hameed, Abdul; Shah, Muhammad R.; Khan, Naveed A. (Medicinal Chemistry, 2020)
Background: Acanthamoeba is an opportunistic pathogen widely spread in the environment. Acanthamoeba causes excruciating keratitis which can lead to blindness. The lack of effective drugs and its ability to form highly resistant cyst are one of the foremost limitations against successful prognosis. Current treatment involves mixture of drugs at high doses but still recurrence of infection can occur due to ineffectiveness of drugs against the cyst form. Pyridine and its natural and synthetic derivatives are potential chemotherapeutic agents due to their diverse biological activities. Objective: To study the antiamoebic effects of four novel synthetic dihydropyridine (DHP) compounds against Acanthamoeba castellanii belonging to the T4 genotype. Furthermore, to evaluate their activity against amoeba-mediated host cells cytopathogenicity as well as their cytotoxicity against human cells. Methods: Dihydropyridines were synthesized by cyclic dimerization of alkylidene malononitrile derivatives. Four analogues of functionally diverse DHPs were tested against Acanthamoeba castellanii by using amoebicidal, encystation and excystation assays. Moreover, Lactate dehydrogenase assays were carried out to study cytopathogenicity and cytotoxicity against human cells. Results: These compounds showed significant amoebicidal and cysticidal effects at 50 μM concentration, whereas, two of the DHP derivatives also significantly reduced Acanthamoebamediated host cell cytotoxicity. Moreover, these DHPs were found to have low cytotoxicity against human cells suggesting a good safety profile. Conclusion: The results suggest that DHPs have potential against Acanthamoeba especially against the more resistant cyst stage and can be assessed further for drug development.
Keywords: amoebicidal